2022
DOI: 10.3389/fmicb.2022.884044
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Vein Banding Virus Movement Protein P1 Interacts With Light-Harvesting Complex II Type 1 Like of Fragaria vesca to Promote Viral Infection

Abstract: Chlorophyll a/b-binding protein of light-harvesting complex II type 1 like (LHC II-1L) is an essential component of photosynthesis, which mainly maintains the stability of the electron transport chain. However, how the LHC II-1L protein of Fragaria vesca (FvLHC II-1L) affects viral infection remains unclear. In this study, we demonstrated that the movement protein P1 of strawberry vein banding virus (SVBV P1) interacted with FvLHC II-1L in vivo and in vitro by bimolecular fluorescence complementation and pull-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Moreover, the roles of NbCab-6A in resistance to PVY infection were verified by TRV-based VIGS, and the results showed that the NbCab-6A -silenced plants showed higher PVY resistance. It has been reported that strawberry vein banding virus (SVBV)-encoded P1 can interact with chlorophyll a/b-binding protein of light-harvesting complex II type 1 like (LHC II-1L) and overexpression of LHC II-1L can accelerate SVBV infection ( Xu et al., 2022 ). Therefore, NbCab-6A promoted PVY infection possibly by directly or indirectly interacting with PVY-encoded proteins, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the roles of NbCab-6A in resistance to PVY infection were verified by TRV-based VIGS, and the results showed that the NbCab-6A -silenced plants showed higher PVY resistance. It has been reported that strawberry vein banding virus (SVBV)-encoded P1 can interact with chlorophyll a/b-binding protein of light-harvesting complex II type 1 like (LHC II-1L) and overexpression of LHC II-1L can accelerate SVBV infection ( Xu et al., 2022 ). Therefore, NbCab-6A promoted PVY infection possibly by directly or indirectly interacting with PVY-encoded proteins, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%